The Sensitivity of Lung Disease Surrogates in Detecting Chest CT Abnormalities in Children with Cystic Fibrosis - Sanders, Don B. (2011)
RATIONALE: Chest CT scans detect structural abnormalities in children with cystic fibrosis (CF), even when pulmonary function tests (PFTs) are normal. The use of chest CT is limited in clinical practice, because of concerns over expense, increased resource utilization, and radiation exposure. Quantitative chest radiography scores are useful in detecting mild lung disease, but whether they are sensitive to the presence of CT scan abnormalities has not been evaluated. OBJECTIVE: To determine in a cross-sectional study if quantitative chest radiography is a more sensitive marker of chest CT abnormalities than other lung disease surrogates. METHODS: Brody chest CT scores were calculated for 81 children enrolled in the Wisconsin CF Neonatal Screening Project. We determined the sensitivity for Wisconsin (WCXR) and Brasfield (BCXR) chest radiography scores, PFTs, positive cultures for P. aeruginosa (PA), and parental report of symptoms to detect a Brody score worse than the median score for study participants. MEASUREMENTS AND MAIN RESULTS: The mean FEV(1) for the study population was 91% predicted. Abnormal WCXR and BCXR scores had the highest sensitivity to detect a chest CT score worse than the median; abnormal PFTs, parental report of symptoms, and the presence of PA had much lower sensitivity (p<0.001). CONCLUSIONS: In this cross sectional study, quantitative chest radiography has excellent sensitivity to detect an abnormal chest CT and may have a role in monitoring lung disease progression in children with CF.